Kontribusi Ki Hajar Dewantara dalam Membangun Pendidikan Nasional Indonesia - Firdiana, Linda; Muchasin, Fiki Vendi; Isrofuzain, Isrofuzain; Khoir, Mulyanto Abdullah (Lembaga Yasin AlSys, 2025)
This study is grounded in the significance of Ki Hajar Dewantara’s role in formulating the philosophical foundations of Indonesian education, despite the limited depth of academic exploration into the contribution and contemporary relevance of his thought. The objective of this research is to examine Ki Hajar Dewantara’s educational philosophy, particularly the principles Ing Ngarsa Sung Tulada, Ing Madya Mangun Karsa, and Tut Wuri Handayani, and to analyze their influence on the development of the national education system. Utilizing a qualitative approach, the study employs content analysis and cross-validation of primary and secondary sources, including historical documents, biographical records, and expert interpretations. The findings reveal that Ki Hajar Dewantara’s philosophy serves as a foundational pillar in the formation of character education, participatory leadership, and holistic student development. The establishment of Taman Siswa is a concrete manifestation of these ideas, significantly contributing to expanding educational access, preserving national culture, and fostering national consciousness during the colonial and post-independence periods. Nevertheless, the application of his philosophy in the modern era faces challenges in contextualizing its values within the dynamic landscape of contemporary educational policy and systems. The study concludes that Ki Hajar Dewantara’s educational thought remains highly relevant in addressing current educational challenges, particularly in promoting student-centered learning grounded in cultural values. Its implications include a theoretical contribution to the discourse on national educational philosophy and practical recommendations for educators and policymakers to align educational practices with foundational national values.